A seedsnipe (Aves, Charadriiformes, Thinocoridae) from the Ensenadan Age/Stage (early-middle Pleistocene) of Buenos Aires, Argentina - Picasso, Mariana Beatriz Julieta (2017)
The fossil record of the Charadriiformes in South America is scarce and limited to the Neogene of Argentina and Peru. In the present contribution, we present and describe a nearly complete tarsometatarsus of Thinocorus rumicivorus (Least Seedsnipe) from the Ensenadan Age/Stage (early-middle Pleistocene) of Punta Hermengo, Buenos Aires province, Argentina, which constitutes the youngest record for the species to date. We also compare the material with extant and fossil Thinocoridae. The stratigraphic range of the fossil predates the Matuyama/Brunhes boundary and is coincident with the biozone of Mesotherium cristatum, which indicates a more humid and warmer climate than the present for the species.